Mourning My Mother: An Exploration of the Complex Emotions Elicited by the Terminal Illness of an Estranged Parent - Pedersen, Anne Bettina (Kvinder, Køn & Forskning, 2019)
In 2017, I learned that my estranged mother had been diagnosed with terminal cancer. This article explores the conflicting emotional responses I have had following the decision not to reconnect with my mother, not to provide care for her during her illness, and not to attend her funeral (when the time comes). This study combines my own creative explorations of child neglect, through autophenomenography, with examinations of autobiographical accounts of mother-daughter relationships and literature on family estrangement and the loss of a parent. I suggest that I already ‘read’ myself as a motherless daughter, and that caring, (re)mourning, and (re)grieving for my mother would entail reentering a dysfunctional dyad and opening up past wounds. There appear to be few resources to draw on regarding how to navigate this particular emotional terrain. This article does not intend to provide a prescriptive model for this type of loss, but rather aims at opening up for queer modes of grieving and mourning and suggests that, in some cases, the denial of care for an estranged parent translates into self-care and self-preservation.